The Impact of Preoperative Anemia in Patients Undergoing Cardiac Surgery - (:unkn) unknown (My University, 2020)
INTRODUCTION: The incidence of preoperative anemia in cardiac surgery patients was found to be 26% on average, up to a maximum of 30%. In this study, we aimed to evaluate the relationship between preoperative anemia incidence, mortality and perioperative complications in patients undergoing cardiac surgery.METHODS: Adult patients undergoing coronary bypass surgery due to ischemic heart disease were included. Patient demographics, cardiac reserves, preoperative and postoperative Hemotocrit values, transfusion volume, complications and mortality rates were recorded. Other laboratory tests, type of surgery, re-exploration frequency, intensive care and hospital stay were recorded.RESULTS: The data of 333 patients were evaluated in this study. The incidence of anemia was 43%. Eighty percent of patients received transfusion and 75% of blood transfusions were in anemic group. Perioperative bleeding amount was 715.7±452.3 mL, and the mean amount of bleeding was significantly higher in anemic group (p=0.000). Nine patients were reexplored. The use of Fresh Frozen Plasm in anemic group was higher (p=0.019). There was no difference between groups in terms of mortality, drainage, hospital stay and mortality.DISCUSSION AND CONCLUSION: The incidence of anemia in the preoperative period was found high. Although our study did not lead to an increase in complications, the risks associated with blood transfusion exists. We believe that the awareness of preoperative anemia should be increased.

GİRİŞ ve AMAÇ: Kalp cerrahisi hastalarında preoperatif anemi insidansı ortalama %26 olup maksimum %30'a ulaşmaktadır. Bu çalışmada kalp cerrahisi geçiren hastalarda preoperatif anemi insidansının, mortalite ve perioperatif komplikasyonlar ile ilişkisini değerlendirmeyi amaçladık. YÖNTEM ve GEREÇLER: İskemik kalp hastalığı nedeniyle koroner bypass ameliyatı geçiren erişkin hastalar çalışmaya dahil edildi. Hastaların demografik özellikleri, kardiyak rezervleri, ameliyat öncesi ve sonrası Hemotokrit değerleri, transfüzyon hacmi, komplikasyonlar ve mortalite oranları kaydedildi. Diğer laboratuvar testleri, yapılan cerrahi ameliyat, re-eksplorasyon sıklığı, yoğun bakım ve hastanede kalış süresi kaydedildi. BULGULAR: Bu çalışmada 333 hastanın verileri değerlendirildi. Anemi insidansı %43 idi. Hastaların %80’i kan transfüzyonu aldı ve transfüzyonların %75'i anemik gruptaydı. Perioperatif kanama miktarı 715,7 ± 452,3 mL idi ve ortalama kanama miktarı anemik grupta anlamlı derecede yüksekti (p = 0,000). Dokuz hasta re-eksplorasyon geçirdi. Anemik grupta Taze Donmuş Plazma kullanımı daha yüksekti (p=0,019). Gruplar arasında mortalite, drenaj, hastanede kalış ve mortalite bakımından fark yoktu. TARTIŞMA ve SONUÇ: Çalışmamızda preoperatif dönemde anemi insidansı yüksek bulundu. Komplikasyonlarda artış olmamasına rağmen, kan transfüzyonu ile ilişkili riskler mevcuttur. Sonuç olarak preoperatif anemi konusunda farkındalığın artırılması gerektiğine inanmaktayız.
Kardiyak Cerrahi Geçiren Hastalarda Preoperatif Aneminin Etkisi